Political Leadership Crisis in Pakistan: Causes and Consequences (Journal of Asian Development Studies, 2025)
The main objective of this study is to highlight the causes and consequences of Pakistan’s political leadership crisis. The implications of the 21st century definition of the state is rooted in the dilemma of the structure and institutional system. To throw a Qualitative methodology to explore the fragility of democracy, the crisis of family dysfunction, and the instability among political family systems. The elites either lack leadership at the grassroots level or the struggling elected government is taken over by unelected institutions. The implications of this crisis extend beyond one aspect, resulting in economic stagnation, social unrest, and institutional degradation for various sectors. A key response to the emerging leadership paradox in this era of crisis is to facilitate inclusive, accountable, visionary leaders who will prioritize national interests over private interests. When society is molded by its own idiocy, there can be no solution. Exploring the background of the Pakistani economy, military, and judiciary, this paper contextualizes it with Pakistan's current political framework to establish the importance of reforms and sustainable political stability in the country.